The performance of Takakura composting using food waste from Makanan Ringan Mas Industry - Azhari, Nur Wahidah (2019)
Food waste is the easily biodegradable waste. Without proper management, the waste could create several environment problems. Management of food waste reduces or eliminates adverse impacts on land, contamination of the atmosphere, soil and water. The aim of this study was to investigate the performance of takakura composting methods by utilizing waste generated by Makanan Ringan Mas Industry. Two types of takakura composts were prepared with different decomposing mediums and fermentation liquids. Each reactor was then left to stable for up to 22 weeks and the final product content was determined to evaluate the level of decomposition. Physical, chemical and biological parameters were examined to observe the effectiveness of each reactor. In terms of physical parameters, a maximum temperature of 44 °C was observed in reactor processed food waste. The pH values fluctuated between 6 to 8.5 whereas the moisture content between 40% to 55% in all reactors throughout the composting process. As for chemical parameters except reactor of raw food waste was not achieved satisfactory values. In addition, biological parameters demonstrated the microbial activity during the decomposing process. After a composting period of 22 weeks, slight difference demonstrated between the best values of total kjedahl nitrogen, phosphorus and potassium obtained by research compost in reactor processed food waste were 6300 ppm, 10.57 ppm, 726.07 ppm, respectively while for commercial compost 8400 ppm, 15.45 ppm and 727.81 ppm respectively. In contrast, raw food waste had the lowest total kjedahl nitrogen, phosphorous and potassium values. Nevertheless, all the results obtained indicate that all the composted food wastes along with the decomposing mediums and fermentation liquids were suitable to be used as both soil amendment and organic compost.